Studies of temperature-humidity characteristics of the greenhouse cyber-physical system - Midyk, Andrii-Volodymyr; Lysa, Olha (Видавництво Львівської політехніки, 2020)
The main information parameters of the microclimate of greenhouse premises are substantiated, in particular: air temperature, relative humidity, illumination of greenhouse premises, soil temperature, soil humidity, the concentration of carbon dioxide. The cyber-physical system for vegetables’ cultivation with the regulation of temperature-humidity-insolation regime contains three subsystems, namely the subsystem of temperature control, the subsystem of humidity control, and the subsystem of insolation control. Accordingly, each of them is equipped with a conjugated smart sensor and a smart actuator. As a result, the choice of smart sensors and their location in the greenhouse is considered. CPS’s model has been performed and tested. To assess the uniformity of the temperature in the greenhouse and the points of the sensor's location, the temperature and humidity were measured previously. The defined set of their values were maintained while the CPS’ operation.
Keywords: Cyber-physical system; Measurement; Microcontroller; Smart sensor; Smart actuator; Temperature; Humidity; Insolation